Situation Report: Poland, 6 February 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Church-State Relations: Tension and Problems of Normalization Grzegorz Przemyk's Case Adjourned The Price Issue, or the Poor Get Poorer New Chairman of the Polish Academy of Sciences GDR Eases Tourist Traffic with Poland Sundry Items